2020
DOI: 10.1111/hiv.12886
|View full text |Cite
|
Sign up to set email alerts
|

Integration of HIV services with primary care in Yangon, Myanmar: a retrospective cohort analysis

Abstract: Objectives Integration of HIV care with general healthcare may improve patient engagement. We assessed patient outcomes in four clinics offering HIV care integrated into primary care clinics in Yangon, Myanmar. Methods We carried out a retrospective cohort analysis of 4551 patients who started antiretroviral therapy between 2009 and 2017. Mortality and disengagement from care were assessed using Cox regression. Results People living with HIV presented late with low CD4 counts [median (25th, 75th percentile) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…As treatment adherence was probably good in our cohort, the long delay in VL testing did not have a large negative impact on viral load results. In earlier studies in Myanmar, high retention was also reported [21,30].…”
Section: Discussionmentioning
confidence: 80%
“…As treatment adherence was probably good in our cohort, the long delay in VL testing did not have a large negative impact on viral load results. In earlier studies in Myanmar, high retention was also reported [21,30].…”
Section: Discussionmentioning
confidence: 80%
“…Based upon existing estimates that cryptococcal meningitis prevalence is 6% in patients with CD4 < 100 at the time of antiretroviral initiation, [9] we believe the 76 patients included in this study is representative of the cases with CD4 < 100 (1460 patients) within the MAM cohort during this study period. The outcomes described suggest that mortality within the first 2 and 10 weeks of treatment (0 and 7%) were much lower than comparable published data on LMIC hospital-based cohorts in (1 7% at two weeks and 34% at 10 weeks [13,14]).…”
Section: Discussionmentioning
confidence: 96%
“…Published literature concentrates on hospital-based mortality outcomes for confirmed cryptococcal meningitis cases. However, in resourceconstrained settings outpatient management may be the only option available to deliver life-saving treatment due to social and financial barriers to hospital-based care [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From that time onwards, the people of the Mon country went to worship there. (Tun Aung Chain and Thein Hlaing 1996: 3)…”
Section: A ‘Mon’ and ‘Buddhist Kingdom’mentioning
confidence: 99%